1997
DOI: 10.1080/15216549700203451
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vitamin E and selenium on antioxidant defense in rat heart

Abstract: Heart mitochondria, isolated from rats fed diets deficient or supplemented with vitamin E (E) and/or selenium (Se), were subjected to time-course assays of lipid peroxidation stimulated by ascorbate/ADP/Fe 3.. Mitochondria depleted of a-tocopherol (a-TH) peroxided rapidly as assessed by formation of thiobarbituric acid reactive substances (TBARS). Formation of TBARS was strongly inhibited in mitochondria from rats fed diets supplemented with E. Selenium deficiency, reduced glutathione (GSH), glutathione disulf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
3
1
Order By: Relevance
“…In fact, it has been reported that TBARS and other indices of lipid peroxidation increased in SeD animals. 25,26 Our previous finding that the uptake rate of Fe in the liver of SeD rats changed with time 27 would seem to be in conflict with the present study, in which the Fe uptake did not change. Because the liver was not perfused in the previous case, the Fedistribution in residual blood might have affected the results to some extent.…”
Section: Resultscontrasting
confidence: 55%
“…In fact, it has been reported that TBARS and other indices of lipid peroxidation increased in SeD animals. 25,26 Our previous finding that the uptake rate of Fe in the liver of SeD rats changed with time 27 would seem to be in conflict with the present study, in which the Fe uptake did not change. Because the liver was not perfused in the previous case, the Fedistribution in residual blood might have affected the results to some extent.…”
Section: Resultscontrasting
confidence: 55%
“…The enzymes involved in the last steps of the biosynthetic pathway are exclusively located in the inner mitochondrial membrane; then, ubiquinone uses the endo-exocytic pathway to distribute among cell membranes moving from and to mitochondria through mitochondria-associated membranes, and reaching the plasma membrane (85). Therefore, changes of ubiquinone concentration in plasma membranes may arise either from biosynthesis or translocation from intracellular reservoirs, such as the endoplasmic reticulum and mitochondria (257). Further, the amount of ubiquinone in membranes is also dependent on dietary vitamin E, selenium, and ubiquinone (162,216).…”
Section: Intermediate Electron Carriersmentioning
confidence: 99%
“…High levels of other antioxidants can only delay but not prevent peroxidative damage if membrane-based vitamin E is deficient [102]. Lower vitamin E levels are found in patients with multiple risk factors for coronary disease suggesting impaired or exhausted antioxidative defense [103].…”
Section: Vitamin Ementioning
confidence: 99%